Kang Youwei and Italy in the Beginning of the 20th Century: Comprehension of the Politics of the West by the Traditional Confucian Thinker - D. E. Martynov (Сравнительная политика)
The article deals with the theoretical treatises written by Kang Youwei (1858 — 1927) in exile and devoted to the understanding of Western social and political reality from the standpoint of a bearer of traditional Chinese culture and Neo-Confucian philosophy. First of all, these are “Travelogue to Italy” (Yidali youji, 1904) and “Impartial Words on Republicanism” (Gonghe pingyi, 1918). Kang Yuwei’s thinking is characterized by attention to the Confucian binary opposition si — gong (private — general), which he transferred to both civilizational development and international politics. In other words, the Western path of development, which consist national imperialist states based on economic, social and foreign policy competition and individualism (“private”), was opposed to the monolithic ancient China, whose society and politics are based on the principles of “community” and unity. Kang Youwei perceived the political reality of Western countries from the standpoint of traditional Chinese historiography, which was intended to serve as a base of positive and negative precedents for use by the ruler in the name of the common good and the harmonization of society. In Kang Youwei’s system of historical views, modern Italy and Germany were very important for illustrating the principle of consolidation of political entities and the merging of small and weak states into large empires. Methodologically, this was formalized as the assignment of Germany, Italy and China to the same ontological category (tong lei).